INJECTION OF AUTOLOGOUS WHOLE BLOOD VERSUS CORTICOSTEROID FOR LATERAL EPICONDYLITIS: A COMPARATIVE STUDY - KHAN, AWEZ; WAHID, BHIMANI FAHAD; TIWARI, MUKESH; KANOJI, RAJESH KUMAR; SUTHAR, PRADEEP KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective is to compare the efficacy, in terms of pain relief and functional improvement, of autologous whole blood and corticosteroid injection in managing lateral epicondylitis (Tennis elbow). Methods: This was a comparative study conducted in Department of Orthopedics, National Institute of Medical Sciences Jaipur, Rajasthan, India. Eighty patients diagnosed to be having lateral epicondylitis were included in this study on the basis of predefined inclusion and exclusion criteria. The patients were divided into 2 groups on the basis of whether they were given autologous whole blood (Group B) or corticosteroid injection (Group S). Efficacy of both the treatment modality was compared in terms of Pain relief (as assessed by reduction in visual analogue score [VAS] score) and functional improvement (as assessed by improvement in Mayo Elbow performance score). SSPS 22.0 software was used for statistical analysis and p<0.05 was taken as statistically significant. Results: A total of 80 patients were included in this study out of which there were 37 (46.25%) males and 43 (53.75%) females with a M: F ratio of 1:1.16. The mean age of patients in group B and group S was found to be found to be 52.36±9.98 years and 48.46±10.12 years, respectively. The mean age of patients in both the groups was found to be comparable with no statistically significant difference (p=0.0866). At the time of 4 weeks, 8 weeks, and 12 weeks follow–up, the mean VAS score in Group B was less as compared to group S and the difference was found to be statistically highly significant (p<0.0001). At the time of 4 weeks, 8 weeks, and 12 weeks’ follow-up, the mean MEPS in Group B was more as compared to group S, and the difference was found to be statistically significant (p<0.05). Conclusion: For lateral epicondylitis, whole blood injection demonstrated superior efficacy in terms of pain relief and functional improvement as compared to injection of corticosteroid.